SCIENTIFIC VIEWS ON INTEGRATION PROCESSES IN CENTRAL ASIA IN TURKEY - Toshev Solejon Ahmatjonovich (Western European Studies, 2025)
In the article Central In Asia integration processes In Turkey scientific in research , analysis centers in the analyses , and periodic in the press lighting issue comparative analysis based on statement done
Keywords: Central Asia; integration processes; Turkish historiography